Analysis of pedestrian behavior in individual and group displacements - Acela, Leidy Marcela Baron (2019)
Many of our actions are influenced by the social context, in particular, by the actions carried out by other people. Within pedestrian flows, people tend to walk in groups such as friends, couples, or families. In this sense, an important aspect that needs to be analyzed is the influence of the relationship between the properties of each person and the collective properties resulting from the social interaction between people. The main goal of this work is to develop a methodology to acquire and analyze empirical data about the movement (characteristics of the gait and speed) and pedestrians’ actions (distance, spatial formation), through the realization of field experiments before and during road crossings in urban areas using wearable inertial sensors and video recordings.